2019
DOI: 10.23917/indigenous.v4i2.7970
|View full text |Cite
|
Sign up to set email alerts
|

Pengalaman self regulated learning siswa untuk menghadapi ujian

Abstract: The completeness of a program in the education unit (in this case secondary school) will end with the holding of an evaluation of learning outcomes or exams, which are school exams and national exams, students will increase their learning activities in preparation for being able to take exams and try to produce satisfying achievements. This study aims to explain students' experiences in practicing self-regulated learning (SRL), which includes students' readiness in an active, constructive process, able to set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 16 publications
1
5
0
3
Order By: Relevance
“…The third factor is the learning process, where the learning process also determines whether learners can be categorized as autonomous learners or not because, in the learning process, there are learning activities that will support the development of autonomous learners. This is following previous researchers who stated that learner autonomy is formed through various teaching and learning process activities and directing these learning activities towards autonomy learning, such as independent activities, project-based assignments, independent assignments, and other learning activities so that learners feel independent and responsible for the assignments that have been given (Andriani et al, 2018;Anita 2016;Ardi, 2017;Darsih, 2018;Septianingrum et al, 2018;Sudinaji & Kumaidi, 2019). The fourth factor is learner training.…”
supporting
confidence: 58%
See 4 more Smart Citations
“…The third factor is the learning process, where the learning process also determines whether learners can be categorized as autonomous learners or not because, in the learning process, there are learning activities that will support the development of autonomous learners. This is following previous researchers who stated that learner autonomy is formed through various teaching and learning process activities and directing these learning activities towards autonomy learning, such as independent activities, project-based assignments, independent assignments, and other learning activities so that learners feel independent and responsible for the assignments that have been given (Andriani et al, 2018;Anita 2016;Ardi, 2017;Darsih, 2018;Septianingrum et al, 2018;Sudinaji & Kumaidi, 2019). The fourth factor is learner training.…”
supporting
confidence: 58%
“…With the variation in the use of online media in learning English, teachers have references to online media sources and increase knowledge so that they are ready for the online learning process which will lead students to study independently. This finding is following Septianingrum et al (2018), andSudinaji andKumaidi (2019) who revealed that the use of various online media or ICT in English learning can provide new insights for teachers and students. In the second indicator regarding the use of teaching materials, the results show that teachers are more likely to instruct students to look for online learning resources that match the material through teacher supervision.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations